Exploring the Link Between Religious Practices and End-User Acceptance Among Muslim Seafarers Using SEM - Nazilul Hamidi; Achmad Bashori; Tri Kismantoro; Baihaqi Baihaqi; Putryanka Septianingsih; Nabiel Muhammad (Dinasti International Journal of Education Management and Social Science, 2026)
This study addresses the limited empirical evidence on the role of religious practices in maritime human resource management (HRM), particularly in relation to the performance and workplace acceptance of Muslim seafarers in multicultural shipping environments. This study aims to examine the relationship between Muslim seafarers’ religious practices and their job performance, adaptability, and end-user acceptance in the global shipping industry. A quantitative survey design was employed, and data were collected from 50 Muslim seafarers using a structured questionnaire. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results indicate that religious practices significantly improve job performance (β = 0.844, p < 0.001) and adaptability (β = 0.592, p = 0.028). However, religious practices do not have a significant direct effect on end-user acceptance (β = 0.024, p = 0.344), and adaptability also has no significant effect on end-user acceptance (β = -0.012, p = 0.564). In contrast, job performance has a positive and significant effect on end-user acceptance (β = 0.478, p = 0.034). These findings suggest that while religious adherence enhances individual effectiveness and social adjustment, professional competence—particularly job performance—remains the primary factor shaping acceptance by shipowners and international stakeholders in the maritime sector.